2016
DOI: 10.1002/adom.201600712
|View full text |Cite
|
Sign up to set email alerts
|

Spindle‐Type Conjugated Compounds Containing Twistacene Unit: Synthesis and Ultrafast Broadband Reverse Saturable Absorption

Abstract: Scheme 1. Molecular structures of DBPy, DPyE, DPyA, and DPDA. Scheme 2. Synthesis of DPyE and DPDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Crystal data and structure refinement for DBD and BBD, 1 H NMR spectrum of DBD and BBD, 13 C NMR spectrum of DBD, high-resolution MS data for DBD and BBD, DFT computations (the geometrical structural and Cartesian coordinates of the DBD and BBD at the ground state and excited state) (PDF) Crystallographic data (CIF) (CIF)…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…Crystal data and structure refinement for DBD and BBD, 1 H NMR spectrum of DBD and BBD, 13 C NMR spectrum of DBD, high-resolution MS data for DBD and BBD, DFT computations (the geometrical structural and Cartesian coordinates of the DBD and BBD at the ground state and excited state) (PDF) Crystallographic data (CIF) (CIF)…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…Conjugated organic molecules have attracted much attention in the field of non-linear optics due to their large non-linear coefficients, ultrafast response rates, large damage thresholds, easy processing, and significant improvement in molecular optical properties through simple substituent changes (Gu et al, 2016 ; Wu et al, 2017a ; Wei et al, 2020 ). The intriguing non-linear optical properties of an organic compound are correlated to its conjugated molecular structure (Kim and Cho, 2009 ; Xiao et al, 2016 ; Sadowski et al, 2017 ; Wu et al, 2017b ). Hence, it is of great importance to establish the relationship between molecular structure and non-linear optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the NLO properties of twistacene and its derivatives have been relatively unexplored, but are highly valued for broadening their applications in the fields such as photonic devices and NIR bio-imaging. Recently, we found that twistacene derivatives are promising NLO materials by studying their third-order nonlinear optical two-photon absorption (TPA) properties in solution using the Z-scan technique [44,45], where the as-synthesized spindletype molecules exhibited a broadband optical limiting capability that the wavelength could range from 500 nm to 1000 nm exposing to femtosecond, picosecond and nanosecond laser pulses. Here, we are more interested in the solid state NLO responses of the twistacenes and their derivatives.…”
Section: Introductionmentioning
confidence: 99%